(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
An efficient protocol was developed for in vitro mass propagation of an important medicinal shrub, Plumbago zeylanica L., (Plumbaginaceae) through direct organogenesis using shoot tip and nodal explants. Best shoot induction was observed on MS basal medium supplemented with 0.5 mg/l BAP, in which 86.4% of nodal explants responded to produce maximum number (12.4 ± 0.66) of shoots per culture. In vitro raised shoots rooted on half strength MS medium with 0.5 mg/l IAA. For acclimatization and transplantation, the plantlets in the rooted culture tubes were kept in normal room temperature for 7 days before transplanting in pots where plantlets were reared for three weeks. The survival rate of regenerated plantlets was 85%. DOI: http://dx.doi.org/10.3329/bjsir.v47i3.13063 Bangladesh J. Sci. Ind. Res. 47(3), 297-302 2012